2021
DOI: 10.3390/polym13030327
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biodegradable Films Loaded with Phages with Antilisterial Properties

Abstract: The inhibitory and bactericidal capacity of Listex P100 bacteriophage has been studied against different concentrations of Listeria monocytogenes in stationary and exponential phases. Three different matrices were employed to developed films incorporating Listex P100: (1) sodium caseinate, (2) sodium alginate mixed with gelatin, and (3) polyvinyl alcohol (PVOH). All the films were successfully developed by casting at room temperature. These active biodegradable films were optical, structural, and thermally cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
(62 reference statements)
2
11
0
Order By: Relevance
“…Although the characteristic shape of HVs (Scheme 1A) could not be resolved in our microscopic images, it can be concluded that the largest fraction of the particles spotted in Figs 3C, 3F, 4A, 4D, and 6A correspond to isolated P100 phages immobilized on Au/AUT. This is supported by the dimensions reported in the literature for isolated active HVs (200-300 nm [37][38][39]), which are consistent with the measurements from our AFM/SEM data, but also by the perfect match between the shape and size of the particles found in our images and those reported for the mica/PEI/T4 slides prepared by Szermer-Olearnik et al [36].…”
Section: Discussionsupporting
confidence: 92%
“…Although the characteristic shape of HVs (Scheme 1A) could not be resolved in our microscopic images, it can be concluded that the largest fraction of the particles spotted in Figs 3C, 3F, 4A, 4D, and 6A correspond to isolated P100 phages immobilized on Au/AUT. This is supported by the dimensions reported in the literature for isolated active HVs (200-300 nm [37][38][39]), which are consistent with the measurements from our AFM/SEM data, but also by the perfect match between the shape and size of the particles found in our images and those reported for the mica/PEI/T4 slides prepared by Szermer-Olearnik et al [36].…”
Section: Discussionsupporting
confidence: 92%
“…Bacteriophages are excellent for preventing or reducing animal illnesses (phage treatment), disinfecting raw materials and carcasses, such as fresh vegetables and fruit, cleaning equipment, and rigid contact interfaces [39]. Using phages in place of antibiotics in agricultural practices is a viable alternative to preserve animal and plant health and reduce the spread of AMR and zoonotic diseases that can be dangerous to consumers [39,40].…”
Section: Bacteriophages Applications In Various Sectorsmentioning
confidence: 99%
“…It was demonstrated that bacteriophage had a strong antibacterial potential against L. monocytogenes with 4.40 and 6.19 log reduction values. To extend bacteriophages to packaging systems, current research has investigated means of maintaining phage stability and activity [33]. Kalkan [34] tested the effectiveness of encapsulated bacteriophages in methylcellulose edible films against Vibrioparahaemolyticus ATCC 17802 in raw fish fillets.…”
Section: Micro-organism Derivedmentioning
confidence: 99%